A mediação didática na construção do conhecimento geográfico: uma análise do processo de ensino e aprendizagem de jovens do ensino médio e da potencialidade do lugar - Bento, Izabella Peracini (2013)
The present paper generates a reflection on the didactic mediation in the construction of geographical knowledge, and analyses, specifically, the teaching and learning process of youngsters in high school and the potentiality of the place. Some goals reached in this research dialogue with the different processes that are in the base of teaching and learning Geography and with some academic researches developed in Brazil, that peer into the reasons which awaken students's interest in learning Geography. It is intended, in that way, to understand how the educator's work exercises an important differential in what concerns an effective and productive teaching, and which presents consistent results in the field of geographical knowledge. It is pressing to look at the geographical culture of youngsters especially when it is invested on the place, as didactic mediation. The place, besides constituting an empiric reference in different areas, is, mostly, an element of geographical reasoning and, because of that, contributes to a didactic mediation desirable to the process of teaching and learning in Geography. With that, it is emphasized the importance of mediation in the construction of geographical cognition, which principles hold their weight in the history and culture of youngsters in school. The geographical concept of “place”, based on a juvenile perspective, is not always considered an element capable of potentiating an approximation between the reality experienced by the students and the more systematized knowledge in the teaching of Geography. For the achievement of this research, the case study constitutes an effective methodological procedure to this investigation, which sediments its reflection in the attendance of classes of two high school teachers in the public school system. The work of these educators, aiming the construction of knowledge in Geography, allowed observations to be made regarding different situations which translate the experiences of the investigated subjects, students and teachers, with a reality, among so many, of the teaching of Geography. The case study was done through a participant observation that, while methodological instrument of intervenient feature, allowed for direct observations of classes to be made, followed by didactic interventions in the observed classes. Semi structured interviews were also conducted with the educators and questionnaires were answered by the students, so that diagnosis profiles of the researched classes could be outlined. Authors such as Callai (1999, 2011a, 2011b, 2000, 2003a, 2003b, 2012), Cavalcanti (1998, 2001, 2002, 2005, 2006, 2011a, 2012b), Libâneo (2000, 2006, 2009a, 2009b, 2011, 2012), Vigotski (2000, 2007, 2010) and other scholars are references that, indispensably, sustain the necessary theoretical foundation to what was proposed to be studied here. Based on some results observed in the course of this investigation, some contributions to the teaching of Geography are highlighted, while greater objective which translates the entire study developed here. In other words, and prognosticating some conclusive evidences, seven principles that guide didactic mediation toward the development of spatial thinking are presented, which are: 1) Reaffirmation of the place as mediating “agent”, which potentiates the construction of knowledge from a multiscale dimension; 2) Adequate articulation of “themes” of the place with the systematized content of Geography; 3) Formation of concepts and of geographical reasoning as a goal of the process of teaching and learning in Geography; 4) Utilization of a differentiated methodology and of other mediating agents beyond the figure of the teacher; 5)Organization of the methodological and theoretical course of Geography classes while intentional activity of the teacher; 6) Problematization as methodological course; 7) Regarding youngsters in school as part of the process of construction of knowledge.